Role of Cardiovascular Computed Tomography in Acute Coronary Syndromes During the COVID-19 Pandemic-Single Center Snapshot Study - Alasnag, Mirvat; Ahmed, Waqar; Al-Nasser, Ibrahim; Al-Shaibi, Khaled (Frontiers in Cardiovascular Medicine, 2021)
Background: In clinical practice, cardiac computed tomography (CCT) has a limited role in acute coronary syndromes (ACS). Several trials evaluated CCT in low and intermediate risk patients presenting to the emergency room (ER) and noted that it was both safe and feasible. During the COVID19 pandemic, it is imperative to adopt a pathway for the evaluation of ACS permitting early discharge, reducing invasive angiography and limiting healthcare worker. This is a single center experience by which CCT was incorporated in the evaluation of patients with ACS. Methods: This is a snapshot study of the first 27 patients who underwent CCT immediately after the lockdown. STEMI and hemodynamically unstable patients were excluded. Those with unstable angina or a NSTEMI were screened for COVID19. The treatment strategy was determined by the CCT results. Patient predisposition, hospital stay and exposure of staff are reported. Results: All CCT images were interpretable. CCT identified critical disease in 7 patients (26%), normal coronary arteries in 11 (41%) and mild to moderate disease in 9 (33%). All patients with normal or mild to moderate disease were assigned to a conservative strategy and discharged within 24 hours. Those with a NSTEMI and critical anatomy were assigned to an additional invasive evaluation with subsequent revascularization. During the course of this study, no transmission to healthcare workers occurred. Conclusion: CCT enabled 80% of patients to be discharged within the first 24 hours, the majority of whom were discharged from the ER. Critical anatomy was identified facilitating early revascularization.